2013
DOI: 10.2174/1874325001307010264
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Failure Among Infected Periprosthetic Patients at a Highly Specialized Revision TKA Referral Practice

Abstract: Deep infection is a serious and costly complication of total knee arthroplasty (TKA), which can increase patient morbidity and compromise functional outcome and satisfaction. Two-stage revision with an interval of parental antibiotics has been shown to be the most successful treatment in eradicating deep infection following TKA.We report a large series by a single surgeon with a highly specialized revision TKA referral practice.We identified 84 patients treated by a two-stage revision. We defined “successful t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Due to the difficulty in treating PJIs, patients are often subjected to a staged protocol requiring two surgeries, the first being removal of the infected prosthetic joint and placement of a temporary spacer impregnated with high doses of antibiotics for several weeks, followed by a second surgery for prosthetic joint re-implantation (11-13). However, patients experiencing a prior PJI are at increased risk for subsequent infections after the placement of a new prosthesis (9, 14). The significant disease burden associated with PJIs and the increasing prevalence of antibiotic-resistant strains, such as methicillin-resistant and vancomycin-intermediate S. aureus (MRSA and VISA, respectively), highlights the importance of investigating alternative treatment paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difficulty in treating PJIs, patients are often subjected to a staged protocol requiring two surgeries, the first being removal of the infected prosthetic joint and placement of a temporary spacer impregnated with high doses of antibiotics for several weeks, followed by a second surgery for prosthetic joint re-implantation (11-13). However, patients experiencing a prior PJI are at increased risk for subsequent infections after the placement of a new prosthesis (9, 14). The significant disease burden associated with PJIs and the increasing prevalence of antibiotic-resistant strains, such as methicillin-resistant and vancomycin-intermediate S. aureus (MRSA and VISA, respectively), highlights the importance of investigating alternative treatment paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…These revision strategies have a re-infection rate of 8.8% and 7.6%, respectively [ 1 ]. Risk factors for the development of recurrent infection after revision surgery include isolation of difficult micro-organisms [ 3 , 4 ], comorbidities [ 3 ], and previous surgeries [ 4 ]. Once any measures to salvage a functional TKA through multiple revision procedures have been exhausted, knee arthrodesis or the above-knee amputation represent the only options to eradicate the infection.…”
Section: Introductionmentioning
confidence: 99%
“…Schwarzkopf et al [30] reported a similar mean time to failure of 438 days following 12 cases of two-stage revision TKA. However, neither of these studies reported the number of failed two-stage revision TKA cases which underwent a prior I&D. The mean failure time in this study was less in the I&D group (136 days) compared with the group without prior I&D (365 days), indicating that the I&D group is more likely to fail earlier.…”
Section: Discussionmentioning
confidence: 93%
“…However, previous studies have either demonstrated a median time to failure between one and 3.6 years [19,27,28] or an average time to failure of 1.2 years. [29,30] It is possible that undetected failures of the two-stage revision TKA occurred beyond four years after surgery in some patients. Lastly, the study was too underpowered to detect a small effect size.…”
Section: Discussionmentioning
confidence: 99%